Alexa, Tell Me More! The Effectiveness of Advertisements through Smart Speakers - Park, Kyuhong; Park, Yongjin; Lee, Junyeong; Ahn, Jae-Hyeon; Kim, Dongyeon (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
Smart speakers enable communication through a voice interface and are among the fastest growing consumer technologies globally; they provide a new and innovative medium for the delivery of interactive advertisements and the sale of products, known as "conversational commerce." However, despite the promising potential of the use of smart speakers as a new advertising channel, little is known about the effectiveness of advertisements made through this medium. Therefore, this article investigates how the distinctive features of smart speakers, namely, interactivity, talker variability, and contextual relevance, influence the effectiveness of advertisements. Through two experiments, we assess the recognition of advertisements for the measurement of advertisements effectiveness through smart speakers. The results of experiment 1 show that the brand and product recognition of advertisements in cases where smart speaker users interact with the advertisements is higher as compared to that of non-interactive advertisements. Experiment 2 further shows that contextual relevance increases the brand and product recognition of advertisement, while talker variability does not affect it. Thus, our findings reveal the nature of the voice interface and provide insights for effective business strategies for advertisements in conversational commerce.
Keywords: SOCIAL PRESENCE; TALKER VARIABILITY; MODERATING ROLE; E-COMMERCE; INTERACTIVITY; INVOLVEMENT; CONSUMERS; CONTEXT; TRUST; RESPONSES